Grammatical Gender in Spoken Word Recognition in School-Age Spanish-English Bilingual Children - Baron, Alisa; Connell, Katrina; Griffin, Zenzi M. (Frontiers in Psychology, 2022)
This study investigated grammatical gender processing in school-age Spanish-English bilingual children using a visual world paradigm with a 4-picture display where the target noun was heard with a gendered article that was either in a context where all distractor images were the same gender as the target noun (same gender; uninformative) or in a context where all distractor images were the opposite gender than the target noun (different gender; informative). We investigated 32 bilingual children (ages 5;6 to 8;6) who were exposed to Spanish since infancy and began learning English by school entry. Along with the eye-tracking experiment, all children participated in a standardized language assessment and told narratives in English and Spanish, and parents reported on their child’s current Spanish language use. The differential proportion fixations to target (target – averaged distractor fixations) were analyzed in two time regions with linear mixed-effects models (LME). Results show that prior to the target word being spoken, these bilingual children did not use the gendered articles to actively anticipate upcoming nouns. In the subsequent time region (during the noun), it was shown that there are differences in the way they use feminine and masculine articles, with a lack of use of the masculine article and a potential facilitatory use of the feminine article for children who currently use more Spanish than English. This asymmetry in the use of gendered articles in processing is modulated by current Spanish language use and trends with results found for bilingual and second-language learning adults.